Pengaruh Penggunaan Bromelin Terhadap Tingkat Pemanfaatan Protein Pakan Dan Pertumbuhan Lele Dumbo (Clarias gariepinus) - -, Nisrinah; -, Subandiyono; Elfitasari, Tita (Journal of Aquaculture Management and Technology, 2013)
The growth of catfish could be improved if the utilization of feed protein by fish can be more efficient. Bromelain is an enzyme of proteases that able to hydrolyze proteins into simpler compounds to be more easily absorbed and utilized of the proteins body. The purpose of the research was to observe the effects of bromelain on protein utility rate and growth of the African catfish (C. gariepinus). The variables measured were feeding efficiency (FE) value, protein efficiency ratio (PER), relative growth rate (RGR), and survival rate (SR). This research used completely randomized design (CRC) with 4 treatments and 3 replicates, i.e. treatment A (did not use bromelin), B (0.75% bromelain), C (1.5% bromelain), and D (2.25% bromelain). The results showed that the influence of the use of bromelin in feed on feeding eficiency (FE), PER, and RGR values were significant (P0.05) on survival rate. Based on the results of treatment A, B, C, and D, it can be concluded that the use of bromelin in feed for C. gariepinus produced better EPP, PER, and RGR values than the feed with no bromelain.